If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3x + 7) + -6(3x + -5) = 10x + 3(2x + -8) Reorder the terms: 4(7 + 3x) + -6(3x + -5) = 10x + 3(2x + -8) (7 * 4 + 3x * 4) + -6(3x + -5) = 10x + 3(2x + -8) (28 + 12x) + -6(3x + -5) = 10x + 3(2x + -8) Reorder the terms: 28 + 12x + -6(-5 + 3x) = 10x + 3(2x + -8) 28 + 12x + (-5 * -6 + 3x * -6) = 10x + 3(2x + -8) 28 + 12x + (30 + -18x) = 10x + 3(2x + -8) Reorder the terms: 28 + 30 + 12x + -18x = 10x + 3(2x + -8) Combine like terms: 28 + 30 = 58 58 + 12x + -18x = 10x + 3(2x + -8) Combine like terms: 12x + -18x = -6x 58 + -6x = 10x + 3(2x + -8) Reorder the terms: 58 + -6x = 10x + 3(-8 + 2x) 58 + -6x = 10x + (-8 * 3 + 2x * 3) 58 + -6x = 10x + (-24 + 6x) Reorder the terms: 58 + -6x = -24 + 10x + 6x Combine like terms: 10x + 6x = 16x 58 + -6x = -24 + 16x Solving 58 + -6x = -24 + 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. 58 + -6x + -16x = -24 + 16x + -16x Combine like terms: -6x + -16x = -22x 58 + -22x = -24 + 16x + -16x Combine like terms: 16x + -16x = 0 58 + -22x = -24 + 0 58 + -22x = -24 Add '-58' to each side of the equation. 58 + -58 + -22x = -24 + -58 Combine like terms: 58 + -58 = 0 0 + -22x = -24 + -58 -22x = -24 + -58 Combine like terms: -24 + -58 = -82 -22x = -82 Divide each side by '-22'. x = 3.727272727 Simplifying x = 3.727272727
| 4.9x^2+8x-30=0 | | .5(2m+6)=.25(8+8m) | | 3x^2-8x=9 | | 4.9x^2+8t-30=0 | | .25(2m-20)=.25(8-8m) | | (3x+7)(5x-1)= | | -35=5-2x+7x | | (2lb-5)-5(4b+4)=-3 | | 10-24d=4-5(2d+9)+3d | | 35-15x=-8x | | 7k+1=2k-1 | | 8w+w+6w= | | 35-15x=8x | | .5(-12m+6)=.25(-20+8m) | | (-8x-7)(-7x-3)= | | N+19=16 | | 6x^2+78x=-216 | | (8x+6)(8x^2+7x+8)= | | 8c*3e= | | -p-2p+3=-6 | | 6+x+-5+2x=x | | 29=2u+13 | | X-3=7-4x | | 6m^2+11m+4=0 | | 5(-2x-4)-3(4+5)=97 | | 0.58+x=133.98 | | 4+y=13-4(y+1) | | x+-17=y | | 6x^4-8x^2+3/8x^2 | | 7-8(k+3)=-10-9k | | 3(x+1)-10=-4(2x-3)+14 | | 4acx*5ax^2*6c= |